Outcome in twin gestations: A prospective observational study - Patil, Swapnil; Utture, Alpana; Mondkar, Jayshree; Goel, Sorabh (Indian Journal of Child Health, 2022)
Background: Incidence of twinning has increased due to the widespread use of assisted reproductive techniques. Twin gestation is associated with many maternal, fetal, and neonatal complications. Objective: The objective of the study is to study the fetal and neonatal complications and outcome of twin pregnancies. Materials and Methods: This is a prospective observational study conducted in a tertiary referral neonatal intensive care unit. 50 consecutive pairs of twins were recruited at the time of admission of the mother to the labor ward. Demographic details of the mother and of the infants were recorded. The outcome of the pregnancy was noted, and the live born infants were followed during the hospital stay and then up till 6 months of corrected gestational age. Results: Incidence of prematurity was 60%. Moderate to severe discordancy was identified in 17 (34%) pairs of twins and 43% infants were born small for gestational age (SGA). Intrauterine Fetal Death was noted in 6 out of 54 infants with discordant growth and 1 out of 46 infants with concordant growth (p=0.046). The overall mortality in our study was 13.9%. Mortality in SGA infants was 23% and 6% in appropriate for gestational age infants (p=0.036). Conclusion: Twinning is associated with high incidence of prematurity, growth discordance, congenital anomalies, intrauterine fetal death, and neonatal mortality.